Workers of all colors unite : race and the origins of American socialism - Costaguta, Lorenzo (Working class in American history., 2023)
"As the United States transformed into an industrial superpower, American socialists faced the vexing question of how to approach race. Lorenzo Costaguta balances intellectual and institutional history to illuminate the clash between two major points of view. On one side, white supremacists believed labor should accept and apply the ascendant tenets of scientific racism. But others stood with Workingmen's Party leader J. P. McDonnel in rejecting the idea that racial and ethnic division influenced worker-employer relations, arguing instead that class played the preeminent role. Costaguta charts the socialist movement's journey through the conflict and down a path that ultimately abandoned scientific racism in favor of an internationalist class-focused and racial-conscious American socialism. As he shows, the shift relied on a strong immigrant influence personified by Curacaoan migrant and future IWW cofounder Daniel De Leon. The racial-conscious movement that emerged became American socialism's most common approach to race in the twentieth century and beyond"--